Increasing Bovine leukemia virus (BLV) proviral load is a risk factor for progression of Enzootic bovine leucosis: A prospective study in Japan - Kobayashi, Tomoko; Inagaki, Yasuko; Ohnuki, Nagaki; Sato, Rina; Murakami, Satoshi; Imakawa, Kazuhiko (Preventive veterinary medicine, 2020)
•Few studies have followed BLV-infected cattle through EBL progression.•High BLV PVL level is a significant risk factor for progression to EBL.•This knowledge might be useful to design a strategy for reducing EBL. Bovine leukemia virus (BLV) belongs to the genus Deltaretrovirus in the family Retroviridae, and is etiologically associated with Enzootic Bovine Leukosis (EBL). The majority of BLV-infected cattle remain asymptomatic throughout their productive lives, whereas approximately 5%–10% of infected cattle develop EBL. Data accumulated recently indicate that whole blood proviral load (PVL) levels of BLV-infected cattle could be an indicator of disease progression in the field. However, a few cross-sectional studies have been reported. Here, we prospectively evaluated 866 cattle enrolled between August 2015 and December 2015, and followed until November 2018, identifying 407 asymptomatic BLV-infected cattle. There were no significant differences in the median PVL level among the category of herd seroprevalence (p = 0.57), herd size (p = 0.19), nor among the category of past EBL history in the herd (p = 0.31). During the study period, 12 cattle developed EBL. The PVL levels of EBL cattle at the time of enrollment were significantly higher than that of cattle that did not progress to EBL (median, 90,695 vs 39,139 copies/105 cells, p = 0.0005). Moreover, the adjusted hazard ratio for the increase in PVL was 2.61 (95% CI, 1.51–4.53) as estimated by the Cox proportional hazards frailty model. These results indicate that a high PVL level is a significant risk factor for progression to EBL, and could potentially be used as an indicator for the identification of cattle to be culled from the herd long before the progression of EBL. This knowledge might be useful to design a strategy for decreasing economic loss from EBL or even eradicating it from herds.